Episcopal Ordination by Imposition of Gospel Book: An Enquiry into Origins - Stewart-Sykes, Alistair (Ex fonte, 2025)
The imposition of the Gospel book in episcopal ordination, first found in Apostolic constitutions, and subsequently widespread, has never satisfactorily been explained. This article explores the possibility that the Vita Herakleidis, a neglected liturgical source, might cast some light on the ritual. Given previous suggestions that the ritual seating of the bishop and the imposition of a hand may be means of ordination with distinct points of origin, the suggestion is made that the imposition of the Gospels was likewise a rite of distinct origin intended, like the imposition of a hand, to indicate appointment. This implies that the imposition of a hand was not the universal and fundamental gesture in episcopal ordinations.